CXCR4 is a Novel Biomarker Correlated With Malignant Transformation and Immune Infiltrates in Gastric Precancerous Lesions - Jiang, Xiaotao; Zheng, Junhui; Liu, Lanxing; Jiang, Kailin; Wen, Yi; Yan, Yanhua; Liu, Yufeng; Zhong, Limei; Huang, Yuancheng; Yao, Zhengyang; Nie, Kechao; Zheng, Zhihua; et al. (Frontiers in Molecular Biosciences, 2021)
Background: As early gastric cancer (EGC) has a far better prognosis than advanced gastric cancer (GC), early diagnosis and treatment are essential. However, understanding the mechanism of the process from gastric precancerous lesion (GPL) becoming to EGC has made little advances. Besides, biomarkers that can monitor the progression of GPL-to-GC are still much insufficient. Methods: Key gene modules associated with GPL progression to EGC were identified by integrating 2 GPL-related datasets GSE55696 and GSE130823 using the WGCNA method. Combining with TCGA-STAD cohort, hub genes were identified. Immunofluorescence was conducted to validate the expression. To explored the implication of hub genes in GPL malignant transformation, correlation test was conducted to identify their co-expression genes, co-expression cytokines and co-expression immune cells. Last absolute shrinkage and selection operator (LASSO) Cox regression was applied to shrink CXCR4-related predictors and construct a prognostic model. Functional enrichment was applied for exploring the potential mechanism. Results: Green module in GSE55696 and yellow module in GSE130823 were regarded as key gene modules associated with GPL progression to EGC and 219 intersection genes from them were mainly enriched in critical immune biological processes. Combining with TCGA-STAD cohort, CXCR4 was identified as a novel biomarker correlated with the malignant transformation of GPL, the positive rate of which was increased with GPL progression according to immunofluorescence. CXCR4 co-expression genes were found mainly involved in regulation of actin. CXCR4 co-expression cytokines were enriched in regulation of chemotaxis, cell chemotaxis, mononuclear cell migration, leukocyte chemotaxis, etc. As for co-expression immune cells, the expression level of CXCR4 was positively correlated with the abundance of macrophage but negatively correlated with that of effector memory T cell and NKT cell during GPL malignant transformation. In addition, CXCR4-related prognostic model was able to predict the prognosis of GC and serve as an independent predictor for overall survival (OS). Conclusions: CXCR4 was a novel biomarker correlated with malignant transformation of GPL and played a vital role in the control of tumor immunity. CXCR4 is possible to serve as a therapeutic target for malignant transformation of GPL.